Zonasi Agroklimat Kabupaten Lampung Tengah untuk Tanaman Padi Berbasis Geographic Information System - Amin, Muhammad; Bramayuda, Taufiq; Ridwan, Ridwan; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2023)
Climate classification in Indonesia is needed to simplify climates, which vary greatly in number. The classification system that is often used in Indonesia is the Schmidt-Ferguson and Oldeman classification. The location of this research is Central Lampung Regency. In determining the climate type of Central Lampung Regency, there are 2 levels of the Schmidt-Ferguson climate suitability category for rice. The Sangat Sesuai (SS) category was 68,087.22 ha from 45.29% of the total ricefield area and for the Sesuai (S) category it was 82,235.04 ha from 54.71% of the total ricefield area. In Oldeman's climate suitability for rice, there are 2 levels of categories. The area for the Sangat Sesuai (SS) is 146,097.48 ha from 97.17% of the total ricefield area and for the Sesuai (S) category it is 4,252.54 ha from 2.83% of the total ricefield area. Rice suitability analysis was carried out to obtain a rice agro-climatic zone based on a ricefield use map and 5 regional limiting factors, namely: 1) Oldeman climate classification, 2) Schmidt-Ferguson climate classification, 3) Temperature, 4) Humidity, and 5) Slope. These 5 factors will be overlaid using Quantum GIS. The result of this analysis is that Central Lampung Regency is dominated by the Sesuai (S) category which is good for agricultural activities, especially rice plants. In the Central Lampung Regency, there are 3 categories of suitability for rice plants. In the Sangat Sesuai (SS) category of 63,780.33 ha of 42.43% of the total area of ricefields, for the Sesuai (S) category of 86,157.08 ha of 57,31% of the total area of ricefield, and in the Tidak Sesuai (TS) category of 389.00 ha of 0.26% of the total area of ricefield. Keywords: Climate, Oldeman, Rice, Schmidt-Ferguson, Scoring, Suitability